Thermo-chemical and mechanical properties of tea tree (Melaleuca alternifolia) fibre reinforced tapioca starch composites - Rodney Jammy (2015)
Melaleuca alternifolia or commonly known as tea tree is a tall shrub or small tree in the plant genus Melaleuca. It is popular for its oil, which is tea tree oil where it has been employed largely in various industries of its antimicrobial properties. Tea tree fibres as the underutilized fibres were investigated physically, chemically and mechanically. From this study, it was found out that the tea tree leaf (TTL) had the highest density 0.42 g/cm3, and had the highest percentage of water absorption, 69.9%. From the tensile strength, tea tree trunk (TTT) gave the highest value, 65.44MPa, followed by tea tree branch (TTB), 48.43MPa and tea tree leaf (TTL), 47.47MPa. The chemical composition of tea tree fibres showed TTT had the highest cellulose content, which is 33.9%, followed by TTB, 27.2% and TTL, 13.5%. Meanwhile, TTL had the highest extractive value, 16.4%, almost 3 times higher than TTB and TTT due to the existence of tea tree oil in TTL. The fabrication of tea tree fibres reinforced tapioca starch (TS) composite successfully developed using casting method. The physical, thermo-chemical, and mechanical properties are undergone in order to get the characterization of the composite. The addition of tea tree fibres do not affect the chemical properties of composite as shown in Fourier transform infrared (FTIR) results, where all of the tea tree fibres and its reinforced composites show same pattern. From the mechanical test, the addition of 5% v/v of tea tree fibre as filler, improved the tensile strength of TS composite up to 34.39% in TTL/TS, 82.80% in TTB/TS and 203.18% in TTT/TS. Thermogravimetric analysis (TGA) proves that tea tree fibres increase thermal stability of composites. Scanning electron microscopy (SEM) shows a good dispersion of the tea tree fibre in the TS matrix. The water absorption and swelling thickness test of all tea tree fibres reinforced composites decreased compared to TS composite. Above all, all parts of the tea tree waste, namely TTL, TTB and TTT have the potential novel fibres which can act as reinforcement in developing a green biocomposite.